2014
DOI: 10.1021/jp4119309
|View full text |Cite
|
Sign up to set email alerts
|

Reversible P3HT/Oxygen Charge Transfer Complex Identification in Thin Films Exposed to Direct Contact with Water

Abstract: Combined systems of semiconducting polymers and aqueous electrolytes are emerging as a new frontier of organic electronics, with many promising applications in neuroscience, biomedicine, and photoelectrochemical cells. A detailed characterization of the effect of direct, prolonged contact with water in working conditions, typically upon visible light illumination, is thus urgently needed. Here, we report a comprehensive study of processes occurring in thin films of regioregular poly(3-hexylthiophene) (rr-P3HT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 43 publications
(63 reference statements)
8
86
0
Order By: Relevance
“…This contribution has been previously assigned to the symmetric C=C stretching mode of the quinoid units of oxidised P3HT35. Appearance of the 1430 cm −1 band has also been observed when P3HT is exposed to the combined action of UV light and oxygen36, and linked to an order/disorder transition taking place upon oxidation of P3HT chains to their quinoid form30. In full agreement with the previously mentioned trend, thermal annealing enhances such a wing, instead of favouring recovery to the pristine form, thus amplifying and possibly consolidating the neutron-induced damage in the polymer (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 60%
“…This contribution has been previously assigned to the symmetric C=C stretching mode of the quinoid units of oxidised P3HT35. Appearance of the 1430 cm −1 band has also been observed when P3HT is exposed to the combined action of UV light and oxygen36, and linked to an order/disorder transition taking place upon oxidation of P3HT chains to their quinoid form30. In full agreement with the previously mentioned trend, thermal annealing enhances such a wing, instead of favouring recovery to the pristine form, thus amplifying and possibly consolidating the neutron-induced damage in the polymer (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 60%
“…The degradation of the active layer of an organic solar cell is mainly driven by the lack of the materials resistances against molecular oxygen, water, temperature and light; 3 the detailed degradation mechanism is often discussed controversially and depends on the material under consideration. [4][5][6][7][8][9][10][11][12] Already the initial degradation can have dramatic consequences on the electrical transport and charge extraction in devices. 13,14 Moreover, it was shown that the electron acceptor (EA) in bulkheterojunction solar cells can affect the stability of electron donor (ED) materials in different ways significantly.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the most favorable route for the formation of SO groups is through the reaction with ROO radicals and that S-OH groups on P3HT's backbone are energetically unfavorable. In another work, 37 DFT-based results were combined with experimental data to show the effects induced by light when P3HT films are in direct contact with water solutions. In particular, the Raman and infrared spectra of an isolated P3HT chain with O 2 and H 2 O molecular defects were computed and compared to the measured ones to reveal that water molecules do not modify the spectra and thus, have no direct involvement to the photoactive doping process.…”
Section: Introductionmentioning
confidence: 99%